Floral anatomy of 12 species of the subtribe Myrciinae (Myrteae, Myrtaceae) - Isabele Pierin Carneiro; Marcela Thadeo; Káthia Socorro Mathias Mourão (Rodriguésia, 2024)
Abstract Myrciinae, one of the nine subtribes of Myrteae, is a monophyletic group and only includes Myrcia. Phylogenetic studies have culminated in the establishment of sections in this genus supported by floral morphological traits. The anatomy of reproductive organs in Myrteae has proven to be important for understanding the evolution in subtribes. We described the floral anatomy of 12 species of Myrcia in eight of the nine sections to identify characteristics that may be useful for species or section delimitation. Herbarium samples and freshly collected material were processed using standard anatomical techniques. Anatomical aspects in all floral whorls that were similar between the species studied, but may occur in species in other subtribes of Myrteae, are the monocyclic pattern of ovarian vascularization, an outer, median and inner parenchymatic ovarian mesophyll, homogeneous mesophyll in the sepal, and campylotropous ovule. Spongy parenchyma in the petal seems to be the most common pattern for Myrteae, but in Pliniinae, a sister subtribe of Myciinae, homogeneous mesophyll is the most frequent type. The discrete differences observed that should be further explored in the subtribe Myrciinae are the presence or absence of unicellular, non-glandular trichomes in the indumentum of the pedicel, gynoecium, hypanthium, sepal, and petal.